Reducing The Fire And Explosion Hazards Of Flame Cutting And Welding In Underground Coal Mines - Preprint 09-007 - W. D. Monaghan (Society for Mining, Metallurgy & Exploration, 2009)
Flame cutting and welding is one of the major causes of fires and explosions in underground U.S. coal mines. On May 20, 2006, a flame cutting operation at the Darby Mine No. 1 led to an explosion that resulted in five fatalities. On January 22, 2003, another explosion caused by flame cutting at the McElroy Mine resulted in three fatalities and three serious injuries. On June 22, 1999, a flame cutting and welding operation at the Loveridge Mine caused a fire that resulted in sealing of the mine for an extended period. Finally, on March 19, 1992, an explosion at the Blacksville No. 1 Mine that was caused by welding resulted in four fatalities. The National Institute for Occupational Safety and Health (NIOSH) conducted a study on fires and explosions in underground U.S. coal mines that were caused by flame cutting and welding operations to determine the root causes of these types of fires and explosions. The methodology included interviewing mining personnel who perform flame cutting or welding operations in underground U.S. coal mines and visiting mines to observe these operations, and MSHA reports of investigations and accidents statistics were analyzed. The results were used to identify and compare differences between flame cutting and welding practices and techniques in small and large mines, Eastern and Western mines, low seam and high seam mines, room and pillar and longwall mines, and between experienced miners and new miners. As a result of this study, best practices and interventions were developed to reduce the number of fires and explosions caused by flame cutting and welding. This paper provides a summary of this work. Disclaimer: The finding and conclusion in this report are those of the authors and do not necessarily represent the views of the National Institute for Occupation Safety and Health.